Intrapericardial immature teratoma in a newborn: a case report. (7th February 2013) - Milovanovic, Vladimir; Lukac, Marija; Krstic, Zoran
Abstract: Intrapericardial teratomas are extremely rare and most often benign tumours. In this paper, we have described a case of intrapericardial teratoma diagnosed prenatally and successfully operated. The presented case is noteworthy as an example of potentially catastrophic cardiorespiratory distress caused by the space-occupying nature of the tumour. A multi-disciplinary approach is mandatory because the tumour most often arises from the ascending aorta and in some cases may require the use of cardiopulmonary bypass.